Self-Efficacy Affects Cancer Patients in Solving Problems, Seeking Support and Avoiding Problems as Coping Mechanisms - Werdani, Yesiana Dwi Wahyu; Silab, Pascalis Arief Ardiansyah (Nurse Media Journal of Nursing, 2020)
Background: Cancer is a disease that causes various physical and mental problems. Being diagnosed with cancer affects the self-efficacy and behavior of individuals to choose a coping mechanism in facing the problem.Purpose: This study aimed to determine the effect of self-efficacy on solving problems, seeking support, and avoiding problems as coping mechanisms in cancer patients.Methods: A cross-sectional study was conducted on 45 cancer patients selected using a total sampling technique from two public health centers in Surabaya, Indonesia. Data were collected using the General Self-Efficacy Scale and Coping Strategy Indicator, and analyzed using the Shapiro Wilk for data normality, and linear regression to determine the effects of self-efficacy on solving problems, seeking support, and avoiding problems with p< 0.05.  Results: The results showed the participants’ rate of self-efficacy levels (M=3.26), and coping mechanism levels in solving problems (M=3.46), seeking support (M=2.88), and avoiding problems (M=3.27), as well as mean scores of self-efficacy (32.6±3.8), solving problems (34.6±3.8), seeking support (31.8±3.7), and avoiding problems (32.7±3.2). Based on the linear regression test, there was a significant effect self-efficacy on solving problems (p<0.001; R2=0.97), seeking support (p<0.001; R2=0.98), and avoiding problems (p<0.001; R2=0.98) as coping mechanisms.  Conclusion: Cancer patients who had high self-efficacy scores would choose solving problems and seeking support as the coping mechanisms, but those with lower scores on self-efficacy prefer to avoid the problems.